Recent advances and prospects of Bacillus amyloliquefaciens as microbial cell factories: from rational design to industrial applications - Luo, Z.; Yan, Y.; Du, S.; Zhu, Y.; Pan, F.; Wang, R.; Xu, H.
Bacillus amyloliquefaciens is one of the most characterized Gram-positive bacteria. This species has unique characteristics that are beneficial for industrial applications, including its utilization of: cheap carbon as a substrate, a transparent genetic background, and large-scale robustness in fermentation. Indeed, the productivity characteristics of B. amyloliquefaciens have been thoroughly analyzed and further optimized through systems biology and synthetic biology techniques. Following the analysis of multiple engineering design strategies, B. amyloliquefaciens is now considered an efficient cell factory capable of producing large quantities of multiple products from various raw materials. In this review, we discuss the significant potential advantages offered by B. amyloliquefaciens as a platform for metabolic engineering and industrial applications. In addition, we systematically summarize the recent laboratory research and industrial application of B. amyloliquefaciens, including: relevant advances in systems and synthetic biology, various strategies adopted to improve the cellular performances of synthetic chemicals, as well as the latest progress in the synthesis of certain important products by B. amyloliquefaciens. Finally, we propose the current challenges and essential strategies to usher in an era of broader B. amyloliquefaciens use as microbial cell factories.
Keywords: BACILLUS AMYLOLIQUEFACIENS; COFACTOR ENGINEERING; DIRECT EVOLUTION; DYNAMIC REGULATION STRATEGIES; INDUSTRIAL APPLICATIONS; METABOLIC ENGINEERING; MICROBIAL CELL FACTORY; MODULAR ENGINEERING; SYNTHETIC BIOLOGY; TRANSPORTER ENGINEERING